PERSPECTIVES ON ISLAMIC CRIMINAL LAW AND POSITIVE INDONESIAN CRIMINAL LAW AGAINST CHILDREN WHO COMMIT CRIMES - Rahmad Alamsyah; Aneesh V. Pillai (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
The factors that cause children to commit delinquency consist of two kinds, namely intrinsic and extrinsic motivation. Intrinsic motivation is encouragement or desire in someone who does not need to be accompanied by stimulants from the outside. Extrinsic motivation is an impulse that comes from outside a person. The punishment for the crime of minors from the perspective of Islamic criminal law and positive criminal law is as follows: Based on Law Number 11 of 2012 concerning the Child Criminal Justice System, which came into force in 2014, it is known that